Diversity of butterflies (Lepidoptera: Papilionoidea) in Universitas Samudra, Langsa - ZAKIYAH HANIFAH SALWA; HERLINA PUTRI ENDAH SARI; KARTIKA APRILIA PUTRI (Jurnal Natural)
Butterflies are one of the animals that have an important role in human life which is currently recorded totaling around 19,022 species in the world and 1,900 species found in Indonesia. Research on butterflies in the campus area in Aceh has not been done too much, so there is a need for research on butterfly diversity in the campus area, especially in Langsa, Aceh. The purpose of this study was to record the species and to analyze ecological factor of butterflies at Universitas Samudra. Sampling was conducted for 5 times once a week from December 2023-January 2024 by purposive random sampling using sweeping techniques and exploring method in 5 observation locations. The results found 30 species from 5 families with a total of 413 individuals. The most common family is family Nymphalidae as many as 15 species (50%) and the most common species found was Appias olferna with a total of 56 individuals. The data found were analyzed for ecological assessment. The result showed the diversity index with H' value of 2.17-2.82 classified as a medium, an evenness index with E value of 0.87-0.94 classified as high, and a dominance index with D value of 0.07-0.19 classified as low.